Drug Delivery System in the Treatment of Diabetes Mellitus - Zhao, Ruichen; Lu, Zhiguo; Yang, Jun; Zhang, Liqun; Li, Yan; Zhang, Xin (Frontiers in Bioengineering and Biotechnology, 2020)
Diabetes mellitus has been described as a chronic endocrine and metabolic disease, which is characterized by hyperglycemia and the coexistence of multiple complications. At present, the drugs widely applied in clinical treatment of diabetes mellitus mainly include insulin, insulin analogs, non-insulin oral hypoglycemic drugs and genetic drugs. Nevertheless, there is still no complete therapy strategy for diabetes mellitus management by far due to the intrinsic deficiencies of drugs and limits in administration routes such as the adverse reactions caused by long-term subcutaneous injection and various challenges in oral administration, such as enzymatic degradation, chemical instability and poor gastrointestinal absorption. Therefore, it is remarkably necessary to develop appropriate delivery systems and explore complete therapy strategies according to the characters of drugs and diabetes mellitus. Delivery systems have been found to be potentially beneficial in many aspects for effective diabetes treatment, such as improving the stability of drugs, overcoming different biological barriers in vivo to increase bioavailability, and acting as an intelligent automatized system to mimic endogenous insulin delivery and reduce the risk of hypoglycemia. This review aims to provide an overview related with the research advances, development trend of drug therapy and the application of delivery systems in the treatment diabetes mellitus, which could offer reference for the application of various drugs in the field of diabetes mellitus treatment.